IMPLEMENTASI RESTORATIVE JUSTICE DALAM PENDIDIKAN KEWARGANEGARAAN UNTUK MEMBENTUK CIVICS RESPONSIBILITY DAN CIVIC SENSIBILITY PADA PELAJAR - Fathurrachman; Dasim Budimansyah; Dwi Iman Muthaqin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the contribution of the restorative justice approach in the context of Civic Education as an effort to build civic responsibility and develop civic sensibility in students. The study used a qualitative approach with data collection techniques through interviews, observations, and documentation studies. The results showed that the application of restorative justice can increase students' responsibility for the consequences of their actions, strengthen legal awareness, and foster mutual respect in social life. Furthermore, the processes of dialogue, mediation, and relationship restoration, which are the main characteristics of restorative justice, provide space for students to understand the impact of their behavior on victims, families, schools, and communities. These experiences encourage the growth of empathy, concern, and social sensitivity as a manifestation of civic sensibility. Thus, restorative justice functions not only as a conflict resolution tool but also as an effective means of character education in shaping young citizens who are responsible, caring, and participate positively in community life.